Pitted keratolysis - a frequently misdiagnosed, mild, infectious disorder of soles - Zuzanna Lewicka-Potocka; Aneta Szczerkowska-Dobosz (Termedia Publishing House, 2016)
Introduction . Pitted keratolysis (PK) is a mild infectious skin disorder caused by Corynebacterium spp., Kytococcus sedentarius or Dermatophilus congolensis . These bacteria produce enzymes that digest keratin, causing superficial lesions in the plantar surface. The disease is predominantly observed in young men. Objective . Pitted keratolysis despite the characteristic presentation of skin lesions is often misdiagnosed. In this article we aimed to remind readers of its clinical aspects and treatment by presenting a typical PK case. Case report. A 35-year-old man was admitted to the dermatological clinic due to skin lesions on both soles. In the physical examination we found multiple crateriform pits, associated with hyperhidrosis and malodour diagnosed as PK. Remission of lesions was observed after treatment with oral erythromycin. Conclusions . The differential diagnosis of plantar skin lesions should include PK. Due to typical clinical manifestation the diagnosis is based on physical examination.